Flow-induced motions of flexible plates: fluttering, twisting and orbital modes. (7th February 2019) - Jin, Yaqing; Kim, Jin-Tae; Fu, Shifeng; Chamorro, Leonardo P.
Abstract : The unsteady dynamics of wall-mounted flexible plates under inclined flows was fundamentally described using theoretical arguments and experiments under various Cauchy numbers $Ca=\unicode[STIX]{x1D70C}_{f}bL^{3}U_{0}^{2}/(EI)\in [7, 81]$ (where $\unicode[STIX]{x1D70C}_{f}$ is the fluid density, $b$ and $L$ are the plate width and length, $U_{0}$ is the incoming velocity, $E$ is Young's modulus and $I$ is the second moment of the area) and inclination angles $\unicode[STIX]{x1D6FC}$ . Three-dimensional particle tracking velocimetry and a high-resolution force sensor were used to characterize the evolution of the plate dynamics and aerodynamic force. We show the existence of three distinctive, dominant modes of tip oscillations, which are modulated by the structure dynamic and flow instability. The first mode is characterized by small-amplitude, planar fluttering-like motions occurring under a critical Cauchy number, $Ca=Ca_{c}$ . Past this condition, the motions are dominated by the second mode consisting of unsteady twisting superimposed onto the fluttering patterns. The onset of this mode is characterized by a sharp increase of the force fluctuation intensity. At sufficiently high $Ca$ and $\unicode[STIX]{x1D6FC}$, the plate may undergo a third mode given by large-scale tip orbits about the mean bending. Using the equation of motion and first-order approximations, we propose a formulation to estimate $Ca_{c}$ as a function of $\unicode[STIX]{x1D6FC}$ ; it exhibits solid agreement with experiments.